Screening and identification of an aflatoxin B1-degrading strain from the Qinghai-Tibet Plateau and biodegradation products analysis - Tang, Ying; Liu, Xiaojing; Dong, Ling; He, Shengran (Frontiers in Microbiology, 2024)
This research aimed to address the issue of aflatoxin B1 (AFB1) contamination, which posed severe health and economic consequences. This study involved exploring unique species resources in the Qinghai-Tibet Plateau, screening strains capable of degrading AFB1. UPLC-Q-Orbitrap HRMS and NMR were employed to examine the degradation process and identify the structure of the degradation products. Results showed that Bacillus amyloliquefaciens YUAD7, isolated from yak dung in the Qinghai-Tibet Plateau, removed 91.7% of AFB1 from TSB-AFB1 medium with an AFB1 concentration of 10 μg/mL (72 h, 37°C, pH 6.8) and over 85% of AFB1 from real food samples at 10 μg/g (72 h, 37°C), exhibiting strong AFB1 degradation activity. Bacillus amyloliquefaciens YUAD7’s extracellular secretions played a major role in AFB1 degradation mediated and could still degrade AFB1 by 43.16% after boiling for 20 min. Moreover, B. amyloliquefaciens YUAD7 demonstrated the capability to decompose AFB1 through processes such as hydrogenation, enzyme modification, and the elimination of the -CO group, resulting in the formation of smaller non-toxic molecules. Identified products include C12H14O4, C5H12N2O2, C10H14O2, C4H12N2O, with a structure consisting of dimethoxyphenyl and enoic acid, dimethyl-amino and ethyl carbamate, polyunsaturated fatty acid, and aminomethyl. The results indicated that B. amyloliquefaciens YUAD7 could be a potentially valuable strain for industrial-scale biodegradation of AFB1 and providing technical support and new perspectives for research on biodegradation products.